2009
DOI: 10.1109/jsen.2009.2030660
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Mode Capacitive Proximity Sensor for Robot Application: Implementation of Tactile and Proximity Sensing Capability on a Single Polymer Platform Using Shared Electrodes

Abstract: In this paper, we report a flexible dual-mode capacitive sensor for robot applications which has two sensing capabilities in a single platform; tactile and proximity sensing capability. The sensor consists of a mechanical structure based on PDMS (Polydimethylsiloxane) and a mesh of multiple copper electrode strips. The mesh is composed of 16 top and 16 bottom copper strips crossed each other to form a 16 16 capacitor array. The proposed sensor is able to switch its function from tactile sensing to proximity se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
110
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(113 citation statements)
references
References 8 publications
3
110
0
Order By: Relevance
“…The performance of our previous sensor does not meet the requirements for the safety sensor [16]. Therefore, we proposed a compliant safety sensor design to meet those requirements in this work.…”
Section: Sensor Designmentioning
confidence: 98%
See 2 more Smart Citations
“…The performance of our previous sensor does not meet the requirements for the safety sensor [16]. Therefore, we proposed a compliant safety sensor design to meet those requirements in this work.…”
Section: Sensor Designmentioning
confidence: 98%
“…In recent years, integrated sensors functioning as both proximity and tactile sensors have been explored as an effort to save cost and space [13][14][15][16]. Göger et al reported a capacitive tactile sensor module that is capable of sensing proximity in combination with another module in the different operational mode [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a capacitive sensor with top electrodes in a comb-like structure can detect the proximity of an object to the fingers (exteroceptive), as well as the collision of the object with the fingers (haptic). This is achieved by monitoring the fringe capacitance of two adjacent electrodes as a function of the changes in the dielectric constant influenced by the proximity of the object to the electrodes (Lee et al, 2009). The principle of operation is shown in Figure 2.…”
Section: Exteroceptionmentioning
confidence: 99%
“…This object can be either a conductor or non-conductor depending on the sensing mechanism of the proximity sensor. Mechanisms that can be used to detect the presence of an object are: inductive [1], optical [2], ultrasonic [3] and capacitive [4]. The inductive mechanism uses an LCR oscillator in which the inductance is altered by an approaching metallic object.…”
Section: Introductionmentioning
confidence: 99%